Efficiency and Safety of Prolonged Levosimendan Infusion in Patients with Acute Heart Failure - Georgios Aidonidis; Ioannis Kanonidis; Vasileios Koutsimanis; Till Neumann; Raimund Erbel; Georgios Sakadamis (Cardiology Research and Practice)
Background. Levosimendan is an inotropic drug with unique pharmacological advantages in patients with acute heart failure. Scope of this study is to determine whether longer infusion patterns without the hypotension-inducing loading dose could justify an effective and safe alternative approach. Methods. 70 patients admitted to the emergencies with decompensated chronic heart failure received intravenously levosimendan without a loading dose up to 72 hours. Clinical parameters, BNP (Brain Natriuretic Peptide) and signal-averaged-ECG data (SAECG) were recorded up to 72 hours. Results. The 48-hour group demonstrated a statistically significant BNP decrease (P<.001) after 48 hours, which also maintained after 72 hours. The 72-hour group demonstrated a bordeline decrease of BNP after 48 hours (P=.039), necessitating an additional 24-hour infusion to achieve significant reduction after 72 hours (P<.004). SAECG data demonstrated a statistically significant decrease after 72 hours (P<.04). Apart from two deaths due to advanced heart failure, no major complications were observed. Conclusion. Prolonged infusion of levosimendan without a loading dose is associated with an acceptable clinical and neurohumoral response.